(untitled) (Academicia Globe: Inderscience Research, 2021)
This article examines the teaching of writing activities for elementary / basic level university students in the lessons of Russian as a foreign language. The proposed types of tasks contribute to the acquisition of knowledge, abilities and skills that serve the gradual formation of communicative written competence among foreign students of the preparatory department (levels A1-B1), which is necessary for the implementation of speech activity in conditions of real social communication in accordance with personal and professional goals.